125k views
1 vote
What is (f−g)(x)
(f−g)(x)=

What is (f−g)(x) (f−g)(x)=-example-1
User Story
by
4.4k points

1 Answer

6 votes

Answer:

3x^5 -2x^4 -x^2 +x -21

Explanation:

We need to subtract g(x) from f(x)

f(x) = 3x^5 +6x^2 -5

g(x) = 2x^4 +7x^2 -x+16

f(x) -g(x) = 3x^5 +6x^2 -5 - (2x^4 +7x^2 -x+16)

Distribute the minus sign

3x^5 +6x^2 -5 - 2x^4 -7x^2 +x-16

I like to line them up vertically

3x^5 +6x^2 -5

- 2x^4 -7x^2 +x-16

---------------------------------------

3x^5 -2x^4 -x^2 +x -21

User Gregoire Ducharme
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.